Metalloradical Compounds with 1,2‐Dipivaloylhydrazido Ligands: Electron Transfer and Alkylation/Protonation Effects - Mondal, Sudipta; Filippou, Vasileios; Bubrin, Martina; Schwederski, Brigitte; Fiedler, Jan; Kaim, Wolfgang (European journal of inorganic chemistry, 2019)
Under oxidative conditions the complexes M(bpy)2Cl2, M = Ru or Os, react with 1,2‐dipivaloylhydrazine H2L = tBuC(O)‐NH‐NH‐C(O)‐tBu to yield the paramagnetic compounds [M(L)(bpy)2](PF6) {1(PF6), M = Ru and 2(PF6), M = Os}. Crystal structures of 1(ClO4) and 2(PF6) reveal an NNCO chelate coordination of L with d(NN) ≈ 1.39 Å. EPR spectroscopy suggests a metal/ligand mixed situation for the unpaired electron, with 29 % (Ru, 1+) or 46 % (Os, 2+) metal spin contribution according to DFT calculations. Both complex cations exhibit reversible one‐electron oxidation and reduction (Kc ≈ 1019 for 1+ and 1012 for 2+) which could also be monitored by IR (νCO) and UV/Vis‐NIR spectroelectrochemistry. These data confirm a metal/ligand orbital mixing MII(L·–) ↔ MIII(L2–), with the osmium analogue favoring the latter alternative. Reaction of Ru(bpy)2Cl2 under non‐oxidizing conditions yields the intermediate (1H)(PF6) which could be oxidatively deprotonated to 1+ or methylated to (1Me)(PF6), both identified by 1H and 13C NMR. While oxidation of (1H)+ proceeds irreversibly due to proton loss, the reversible spectroelectrochemical oxidation of (1Me)+ suggests a metal‐based process RuII(LMe–) → RuIII(LMe–). The results reveal that not only dinuclear complexes of 1,2‐diacylhydrazido ligands but also mononuclear analogues are distinguished by remarkably variable metal/ligand mixed contributions to the frontier orbitals. Stable metalloradical cations 1+ and 2+ with well balanced spin on metal and ligand were experimentally and theoretically characterized. The electron transfer activity of 1+ and 2+ and of protonated (1H)+ or methylated forms (1Me)+ was analyzed.